CCDC82 and neurodevelopment: a novel genetic variant linked to infantile spasms and hypotonia - Zahra Safarian; Shiva Mehrabi; Arghavan Rakhshani Nejad; Sajad Alavimanesh; Pegah Kavousinia; Mohammad Hossein Shushizadeh; Seyedeh Faezeh Hassani; Latifeh Onagh; Abdolazim Sarli; Nahid Rezaie (BMC Medical Genomics)
Abstract Background Neurodevelopmental disorders (NDDs) are a heterogeneous group of conditions characterized by impairments in motor, cognitive, and behavioral functions. Despite advances in genomic sequencing, the genetic basis of many NDDs remains unexplored. CCDC82 encodes a coiled-coil domain-containing protein with an unknown function in the nervous system. This study aims to further delineate the clinical spectrum of CCDC82-related disorders by identifying a novel homozygous nonsense variant in an Iranian family with early-onset hypotonia, infantile spasms, and developmental delay. Methods An 8-month-old male proband of Turkmen descent, born to consanguineous parents, presented with severe hypotonia, spasticity, infantile spasms, and developmental delay. Electroencephalography (EEG) revealed a hypsarrhythmic pattern, and brain MRI showed no significant structural abnormalities. Whole-exome sequencing (WES) was performed on the proband, followed by in silico pathogenicity analysis and segregation studies in the family. Sanger sequencing confirmed the variant, and bioinformatics tools assessed its potential impact. Results WES identified a novel homozygous nonsense variant in CCDC82 (NM_024725.4: c.709 C > T, p.Arg237Ter), which was classified as pathogenic according to ACMG guidelines. This variant is predicted to result in nonsense-mediated decay. This variant was absent in population databases and segregated with the disease phenotype in the family. In silico analyses supported its deleterious effect, and evolutionary conservation studies indicated a conserved role of CCDC82 in neuronal function. Conclusion This study reports a novel pathogenic variant in CCDC82 associated with a severe neurodevelopmental disorder. These findings expand the known phenotypic spectrum associated with biallelic CCDC82 variants, reinforcing its role in early-onset hypotonia and infantile spasms. Further investigations are necessary to confirm its functional role and establish CCDC82 as a novel disease-associated gene.